The effect of conflict management styles on employee performance among Lebanese industrial firms - Aoun, Malak; Mubarak, Sukaina; Hasnan, Norlena (UUMPRESS and Managed by STML, 2020)
This paper studies the effect of conflict management on employees’ performance among some industrial firms in Lebanon. First, conceptual framework was developed based on extensive literature review where conflict management styles and employee performance were discussed comprehensively in terms of definitions and related previous studies. Due to the lack of empirical studies in the Lebanese industrial sector, this empirical study was conducted to test the proposed research hypotheses. Thus, a quantitative approach was adopted through conducting an online survey among 93 employees from three different industrial organizations specialized in producing construction materials, plastics, and wood and metal furniture in Lebanon. The response rate was limited due to COVID-19 Pandemic, where only 63 employees responded. Data analysis was conducted through SPSS. Descriptive statistics were obtained and research hypotheses were tested using Pearson correlation and regression analysis. The results obtained showed that in general, conflict management has positive and significant effect on employees’ performance but to a weak extent. Particularly, only collaborative, compromising and accommodating styles had weak positive correlation with employee performance. Future surveys may involve more companies on a larger geographical scale, and include additional number of workers, for the purpose of attaining more reliable results.